IDENTIFICATIONS OF DIFFICULTIES FACED BY MAHAKARYA ASIA UNIVERSITY STUDENTS IN SPEAKING ENGLISH - Wijayanti, Anita (Dialectical Literature and Educational Journal, 2022)
The aims of this research are to describe (1) linguistic factors that affect students’ difficulty in speaking and (2) internal and external factors that are contributive to the difficulty in speaking English faced by second semester students who took speaking class. The type of the study was descriptive qualitative. The object of the research was second semester students who took speaking class. In this study, the researcher took 31 students as the respondents. The instruments of the research were questionnaire and interview. Technique and data analysis were identifying the difficulties encountered by the students in the speaking class, classifying those difficulties, presenting and analyzing the data in, and discussing. The study reported that difficulties in speaking English were classifiable as linguistic, internal, and external factors. The linguistic factors affecting speaking difficulties were the lack of sufficient masteries of required vocabulary, grammar, and pronunciation and intonation. The internal factors hindering the learning of speaking were the detrimental over influence of the first language and the lack of either or both self-motivation and practice. The external factors were insufficient encouragement and driving force from lecturer, inadequate support from other fellow students, and problems